Prefrontal Dopaminergic Regulation of Cue-Guided Risky Decision-Making Performance in Rats - Yang, Minzhe; Fu, Qiangpei; Ma, Chaolin; Li, Baoming (Frontiers in Behavioral Neuroscience, 2022)
Risky decision-making is the decision made by individuals when they know the probability of each outcome. In order to survive in unpredictable environments, it is necessary for individuals to assess the probability of events occurring to an make appropriate decisions. There are few studies on the neural basis of risky decision-making behavior guided by external cues, which is related to the relative paucity of animal behavioral paradigms. Previous studies have shown that the prefrontal cortex (PFC) plays a key role in risk-based decision-making. The PFC receives projections from the dopamine (DA) system from the ventral tegmental area of the midbrain. The mesocorticolimbic DA system regulates the judgments of reward and value in decision-making. However, the specific receptor mechanism for prefrontal DA regulation of cue-guided risky decision-making behavior remains unclear. Here we established a cue-guided risky decision-making behavioral paradigm (RDM task) to detect the behavior of rats making decisions between a small certain reward and a large uncertain reward in a self-paced manner. The D1 receptor antagonist SCH-23390 (5 mM) or agonist SKF-82958 (5 mM), and the D2 receptor antagonist thioridazine hydrochloride (5 mM) or agonist MLS-1547 (5 mM) was injected into the mPFC, respectively, to investigate how the behavior in the RDM task was changed. The results showed that: (1) rats were able to master the operation of the cue-guided RDM task in a self-paced way; (2) a majority of rats were inclined to choose risk rather than a safe option when the reward expectations were equal; and (3) risk selection was reduced upon inhibition of D1 receptors or stimulation of D2 receptors, but increased upon stimulation of D1 receptors or inhibition of D2 receptors, suggesting that the RDM performance is regulated by D1 and D2 receptors in the mPFC. The present results suggest that DA receptors in the mPFC of rats are involved in regulating cue-guided RDM behavior, with differential involvement of D1 and D2 receptors in the regulation.